Analysis of Plant-Based Culinary Program Design to Improve Vocational High School Students Competence - Maharani, Rachel Tania; Basyirun, Basyirun (Universitas Negeri Semarang, 2025)
Global culinary trends indicate a significant increase in demand for plant-based cuisine in response to health, sustainability, and ethical concerns. This creates an urgent need for professionals competent in plant-based culinary processing. This article analyzes the design of plant-based culinary training programs at Vocational High Schools (SMK) in Indonesia to enhance student competency to meet the needs of the modern culinary industry. The method used is descriptive qualitative, based on a literature review and curriculum documents. The analysis reveals competency gaps, particularly in aspects of plant-based product innovation, advanced processing techniques, in-depth nutritional literacy, and environmental awareness. Recommendations for program development include the integration of technical skills, creativity, entrepreneurship, and an understanding of sustainability to address global market dynamics. The implementation of a holistic program is expected to increase the competitiveness of vocational high school graduates in the culinary sector, which is increasingly shifting toward healthy and environmentally friendly food options